Pengaruh literasi keuangan dan sikap keuangan terhadap perilaku pengelolaan keuangan dengan locus of control sebagai variabel intervening - Wardani, Leni Ayu; Fitrayati, Dhiah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the direct and indirect effects of financial literacy and financial attitudes on how people handle their money, with locus of control functioning as an intervening variable. Students majoring in economic education at the State University of Surabaya in 2018 are the sample population. The Slovin formula was used to estimate the exact sample size to be collected, with a margin of error of 5%. The non-probability approach is mixed with the purposive sampling method in the sampling method. In this investigation, 155 different samples were used for analysis. During the data processing procedure, WarPLS equation type 7.0 was used for structural modeling. Financial literacy does not have an instant effect on a person's sense of control over their life, according to the conclusions of the observational discussion. The degree to which a person is financially literate has little bearing on how they handle their money. Financial attitudes have a direct impact on locus of control. People's attitudes towards money have a direct impact on how they manage their finances. Locus of control has a considerable impact on financial management behavior. While the direct influence of the two components, including financial literacy, has no effect on locus of control behavior in financial management, the indirect effect of this component does. Financial attitudes are influenced by where people position their locus of power, which has an indirect effect on how they manage their money